2005
DOI: 10.1182/blood-2004-08-3251
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of long-term sepsis-induced immunosuppression by dendritic cells

Abstract: Severe sepsis leads to long-term systemic and local immunosuppression, which is the cause of a number of complications, including pulmonary infection. A therapeutic strategy that reverses this immunosuppression is required, given the ongoing high mortality rate of patients who have survived a severe sepsis. The present study demonstrates that experimental severe sepsis renders the lung susceptible to a normally innocuous Aspergillus fumigatus fungus challenge, due to a dominant lung type 2 cytokine pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
116
1
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 44 publications
6
116
1
4
Order By: Relevance
“…are susceptible to a normally innocuous pathogens, and that the transfer of bone-marrow derived DC (essentially composed of mDC) prevented lethal infection (31). These data suggest that postseptic immunosuppression may be due at least in part to the persistent depletion of mDC.…”
Section: Dendritic Cells In Severe Sepsismentioning
confidence: 74%
See 1 more Smart Citation
“…are susceptible to a normally innocuous pathogens, and that the transfer of bone-marrow derived DC (essentially composed of mDC) prevented lethal infection (31). These data suggest that postseptic immunosuppression may be due at least in part to the persistent depletion of mDC.…”
Section: Dendritic Cells In Severe Sepsismentioning
confidence: 74%
“…Several studies in murine models strongly suggests that a deviated DC behavior could account for immunosuppression observed during sepsis, (26)(27)(28)(29) and that a proper DC function is required for a successful outcome to sepsis (30,31). On the other hand, available data on human are very limited (32).…”
mentioning
confidence: 99%
“…Forty to 50% losses of both total (CD11c high ) and lymphoid (CD8␣ ϩ ) DC populations were seen within 24 h. Similar results have been observed by others (11,12), and Hotchkiss et al (13) have reported an increased loss of DCs from the spleens of patients who had died from sepsis. Furthermore, the intrapulmonary installation of bone marrow-derived DCs prevented lethal Aspergillosis infection in septic animals (14), suggesting a functional role for DCs in opportunistic fungal infections in the lung during sepsis.…”
mentioning
confidence: 99%
“…The dysfunction of splenic DC during acute sepsis develops into a chronic dysfunction that is maintained even after resolution of the primary infection and is associated with an impaired capacity of DC to drive an effective Th1 response (15,16). Previous studies have shown that post-septic mice can be rescued from lethal secondary infections by a treatment with DC from naive mice (16)(17)(18). These findings led to the assumption that the enhanced susceptibility of post-septic mice to secondary infections is mediated by the chronic dysfunction of DC.…”
mentioning
confidence: 99%